Prostate cancer methods and protocols - Russell, Pamela J; Ed. Jackson, Paul; Ed (Humana Press, 2003)
A collection of basic and advanced molecular methods that reveal those markers essential for diagnoses of specific diseases. The techniques range from in vitro methods to in vivo models of prostate cancer, and include new methods for the accurate diagnosis of prostate cancer, and proteome and microarray analyses.